Composition
Patent Information
- Application Number
- JP2023136125
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-24
- Publication Date
- 2025-03-07
AI Technical Summary
【0012】 本発明に係る組成物によれば、貯蔵安定性に優れるとともに、得られる塗膜の透明性にも優れており、組成物に含まれる重合体粒子(A)がバインダーとしての特性を発現することで良好な塗膜を形成することができる。
Smart Images

Figure 2025030642000001 
Figure 2025030642000002 
Figure 2025030642000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition containing polymer particles. [Background technology]
[0002] Compositions containing polymer particles such as latex are widely used as binders in the fields of paper coating, carpet backsizing, wood products such as plywood and veneer, battery electrodes, tire cords, and the like (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2022-124473 A [Patent Document 2] International Publication No. 2021 / 006211 Summary of the Invention [Problem to be solved by the invention]
[0004] However, in the composition containing such polymer particles, the polymer particles tend to settle when stored for a long period of time, and storage stability is still an issue. In addition, in various applications such as those described above, when a coating film is formed by applying a composition containing polymer particles and then dried, the coating film may whiten.
[0005] Some aspects of the present invention provide a composition containing polymer particles that has excellent storage stability and also provides a coating film that is excellent in transparency. [Means for solving the problem]
[0006] The present invention has been made to solve at least a part of the above-mentioned problems, and can be realized in any of the following aspects.
[0007] One aspect of the composition according to the present invention is A composition comprising polymer particles (A) and a liquid medium (C), The polymer particles (A) have a repeating unit (Ma) derived from methyl (meth)acrylate and a repeating unit (Mb) represented by the following general formula (1), The content of the polymer particles (A) having a particle size of 0.5 μm or more in the composition is 1×10 5 pieces / mL~5,000×10 5 pieces / mL. [ka] (In formula (1), R 1 represents a hydrogen atom or a methyl group, and R 2 represents an alkyl group having 4 to 10 carbon atoms.
[0008] In one embodiment of the composition, The polymer particles (A) may have a number average particle size of 30 nm to 600 nm.
[0009] In any of the above-described embodiments of the composition, The THF insoluble content of the polymer particles (A) may be 60% by mass or more based on 100% by mass of the polymer particles (A).
[0010] In any of the above-described embodiments of the composition, Furthermore, the polyvalent anion (B) may be contained in an amount of 300 ppm to 2,000 ppm.
[0011] In any of the above-described embodiments of the composition, The polyvalent anion (B) is SO4 2- may be also possible. Effect of the Invention
[0012] The composition according to the present invention has excellent storage stability and the coating film obtained has excellent transparency. The polymer particles (A) contained in the composition exhibit binder properties, making it possible to form a good coating film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Preferred embodiments of the present invention will be described in detail below. Note that the present invention is not limited to the following embodiments, and includes various modified examples that are implemented within the scope of the present invention.
[0014] In this specification, "(meth)acrylic" refers to "acrylic" or "methacrylic". Furthermore, "(meth)acrylate" refers to "acrylate" or "methacrylate".
[0015] In this specification, a numerical range described using "X to Y" means that the numerical range includes the numerical value X as the lower limit and the numerical value Y as the upper limit.
[0016] 1. Composition A composition according to one embodiment of the present invention is a composition containing polymer particles (A) and a liquid medium (C), the polymer particles (A) having a repeating unit (Ma) derived from methyl (meth)acrylate and a repeating unit (Mb) represented by the following general formula (1), and the content of the polymer particles (A) having a particle size of 0.5 μm or more in the composition is 1×10 5 pieces / mL~5,000×10 5 pieces / mL. [ka] (In formula (1), R 1 represents a hydrogen atom or a methyl group, and R 2 represents an alkyl group having 4 to 10 carbon atoms. Components that may be contained in the composition according to this embodiment will be described in detail below.
[0017] 1.1. Polymer particles (A) The composition according to the present embodiment contains polymer particles (A). The composition according to the present embodiment is preferably in the form of a latex in which the polymer particles (A) are dispersed in a liquid medium (C). .
[0018] The repeating units constituting the polymer particles (A), the physical properties of the polymer particles (A), and the synthesis method will be described below in that order.
[0019] 1.1.1. Repeating units constituting polymer particles (A) The polymer particles (A) have a repeating unit (Ma) derived from methyl (meth)acrylate (hereinafter also simply referred to as "repeating unit (Ma)") and a repeating unit (Mb) (hereinafter also simply referred to as "repeating unit (Mb)") represented by the following general formula (1). [ka] (In formula (1), R 1 represents a hydrogen atom or a methyl group, and R 2 represents an alkyl group having 4 to 10 carbon atoms.
[0020] The content of the repeating unit (Ma) is preferably 20 to 95% by mass when the total of the repeating units contained in the polymer particles (A) is taken as 100% by mass. The lower limit of the content of the repeating unit (Ma) is more preferably 30% by mass, and particularly preferably 35% by mass. The upper limit of the content of the repeating unit (Ma) is more preferably 90% by mass, and particularly preferably 85% by mass. By containing the repeating unit (Ma) within the above range, the polymer particles (A) exhibit good storage stability while exhibiting the properties (binding strength) of a binder.
[0021] Specific examples of monomers that provide the repeating unit (Mb) include (meth)acrylic acid alkyl (C4-C10) esters such as n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, and decyl (meth)acrylate, and may be one or more selected from these. Of these (meth)acrylic acid alkyl (C4-C10) esters, one or more selected from n-butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate are preferred.
[0022] The content of the repeating unit (Mb) is preferably 1 to 75% by mass when the total of the repeating units contained in the polymer particles (A) is taken as 100% by mass. The lower limit of the content of the repeating unit (Mb) is more preferably 3% by mass, and particularly preferably 5% by mass. The upper limit of the content of the repeating unit (Mb) is more preferably 70% by mass, and particularly preferably 60% by mass. By containing the repeating unit (Mb) within the above range, the polymer particles (A) exhibit good storage stability while exhibiting the properties (binding strength) of a binder.
[0023] In addition to the repeating units (Ma) and (Mb), the polymer particles (A) may have repeating units derived from other monomers copolymerizable therewith. Examples of such repeating units include repeating units derived from α,β-unsaturated nitrile compounds, repeating units derived from aromatic vinyl compounds, and repeating units derived from unsaturated carboxylic acids. , repeating units derived from unsaturated carboxylic acid esters (excluding repeating units (Ma) and repeating units (Mb)), and repeating units derived from α,β-unsaturated amides.
[0024] Specific examples of the α,β-unsaturated nitrile compound include acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, α-ethylacrylonitrile, vinylidene cyanide, etc., and may be one or more selected from these. Among these, it is preferable to use one or more selected from acrylonitrile and methacrylonitrile, and more preferable to use acrylonitrile.
[0025] The content of the repeating units derived from the α,β-unsaturated nitrile compound is preferably 35% by mass or less, and more preferably 3 to 15% by mass, when the total amount of the repeating units contained in the polymer particles (A) is taken as 100% by mass.
[0026] Specific examples of the aromatic vinyl compound include styrene, α-methylstyrene, p-methylstyrene, vinyltoluene, chlorostyrene, 1-ethyl-2-vinylbenzene, divinylbenzene, sodium p-styrenesulfonate, etc., and the aromatic vinyl compound may be one or more selected from these. Of the above, styrene is particularly preferred as the aromatic vinyl compound.
[0027] The content of the repeating units derived from the aromatic vinyl compound is preferably 5 to 45 mass%, and more preferably 10 to 30 mass%, when the total of the repeating units contained in the polymer particles (A) is taken as 100 mass%.
[0028] Specific examples of the unsaturated carboxylic acid include mono- or dicarboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, etc., and may be one or more selected from these. In particular, it is preferable to use one or more selected from acrylic acid, methacrylic acid, and itaconic acid.
[0029] The content of the repeating units derived from the unsaturated carboxylic acid is preferably 0.1 to 20 mass%, and more preferably 0.5 to 15 mass%, when the total of the repeating units contained in the polymer particles (A) is taken as 100 mass%.
[0030] The unsaturated carboxylic acid ester is preferably a (meth)acrylic acid ester other than methyl (meth)acrylate and alkyl (C4-C10) (meth)acrylate ester. Specific examples of the (meth)acrylic acid ester include ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, benzyl (meth)acrylate, hydroxymethyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, glycidyl (meth)acrylate, ethylene glycol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, allyl (meth)acrylate, and ethylene di(meth)acrylate, and may be one or more selected from these.
[0031] The content of the repeating units derived from the unsaturated carboxylic acid ester (excluding the repeating units (Ma) and (Mb)) is preferably 0.1 to 10 mass%, and more preferably 0.5 to 5 mass%, when the total of the repeating units contained in the polymer particles (A) is taken as 100 mass%.
[0032] Specific examples of the α,β-unsaturated amide compound include (meth)acrylamide, N,N-dimethyl(meth)acrylamide, and N,N-diethyl(meth)acrylamide, and the like can be one or more selected from these.
[0033] The content of the repeating units derived from the α,β-unsaturated amide compound is preferably 0.1 to 20 mass%, and more preferably 0.5 to 15 mass%, when the total of the repeating units contained in the polymer particles (A) is taken as 100 mass%.
[0034] 1.1.2. Physical properties of polymer particles (A) 1.1.2.1. Content of coarse particles The content of polymer particles (A) having a particle size of 0.5 μm or more (herein also referred to as “coarse particles”) contained in the composition according to the present embodiment is 1×10 5 pieces / mL~5,000×10 5 / mL, 100 x 10 5 pieces / mL~3000×10 5 It is preferable that the content of the coarse particles is within the above range. When the composition is applied and dried, the liquid medium (C) evaporates well, and the coating film can be dried effectively. When the content of the coarse particles is within the above range, the generation of foreign matter such as aggregation and precipitation of the polymer particles (A) during storage of the composition can be suppressed, and the storage stability is improved without impairing the quality.
[0035] The content of coarse particles is calculated by directly measuring the number and size of particles in a sample using the SPOS (Single Particle Optical Sensing) method, which measures particles one by one. An example of such a particle size distribution measuring device that uses a particle counting method is the Accusizer 780A (manufactured by Entegris, Inc.).
[0036] The content of coarse particles in the composition according to this embodiment can be controlled to a predetermined content by repeatedly filtering the composition using a filter.
[0037] 1.1.2.2. Tetrahydrofuran (THF) insolubles The THF insoluble content of the polymer particles (A) is preferably 60% by mass or more, more preferably 90% by mass or more, and particularly preferably 95% by mass or more, based on 100% by mass of the polymer particles (A). The THF insoluble content is an index of the solvent resistance and water resistance of the resulting coating film. Therefore, if the THF insoluble content is within the above range, it is considered that the water resistance of the coating film produced using the composition according to this embodiment is good. The method for measuring the THF insoluble content follows the method described in the Examples below.
[0038] 1.1.2.3.Number average particle size The number average particle diameter of the polymer particles (A) is preferably in the range of 30 nm to 600 nm, more preferably in the range of 40 nm to 200 nm. When the number average particle diameter of the polymer particles (A) is within the above range, the surface of the resulting coating film becomes smooth, and a coating film having excellent scratch resistance can be formed.
[0039] The number average particle size of the polymer particles (A) is the particle size (D50) value at which the cumulative frequency of the number of particles when accumulating particles starting from the smallest particle is 50% when the particle size distribution is measured using a particle size distribution measuring device that uses a light scattering method as the measurement principle. Examples of such particle size distribution measuring devices include Coulter LS230, LS100, LS13 320 (all manufactured by Beckman Coulter, Inc.) and FPAR-1000 (manufactured by Otsuka Electronics Co., Ltd.). These particle size distribution measuring devices are capable of evaluating not only the primary particles of the polymer particles but also secondary particles formed by aggregation of the primary particles. Therefore, the particle size distribution measured by these particle size distribution measuring devices can be used as an index of the dispersion state of the polymer particles.
[0040] Transition Temperature The transition temperature of the polymer particles (A) is preferably in the temperature range of -20°C to 150°C, and more preferably -10°C to 135°C, when measured by differential scanning calorimetry (DSC) in accordance with JIS K7121:2012.
[0041] 1.1.3. Method for synthesizing polymer particles (A) The method for synthesizing the polymer particles (A) is not particularly limited, but the polymer particles (A) can be easily prepared, for example, by the emulsion polymerization process described below.
[0042] Examples of monomer components used in the emulsion polymerization step include methyl (meth)acrylate and (meth)acrylic acid alkyl (C4-C10) esters, as well as α,β-unsaturated nitrile compounds, aromatic vinyl compounds, unsaturated carboxylic acids, unsaturated carboxylic acid esters other than methyl (meth)acrylate and (meth)acrylic acid alkyl (C4-C10) esters, and α,β-unsaturated amide compounds.
[0043] In 100% by mass of all monomer components, the content of methyl (meth)acrylate is preferably from 20 to 95% by mass, more preferably from 30 to 90% by mass, and particularly preferably from 35 to 85% by mass.
[0044] In 100% by mass of all monomer components, the content of the (meth)acrylic acid alkyl (C4-C10) ester is preferably 1 to 75% by mass, more preferably 3 to 70% by mass, and particularly preferably 5 to 65% by mass.
[0045] The emulsion polymerization step is carried out in an aqueous medium in the presence of an emulsifier, a polymerization initiator, and a chain transfer agent. Each material used in the emulsion polymerization step will be described below.
[0046] Specific examples of the emulsifier include anionic surfactants such as sulfate salts of higher alcohols, aliphatic sulfates, alkylbenzene sulfonates, alkyl diphenyl ether disulfonates, aliphatic sulfonates, aliphatic carboxylates, aliphatic phosphate salts, aliphatic phosphate salts, dehydroabietic acid salts, naphthalenesulfonic acid-formaldehyde condensates, sulfate salts or phosphate salts having a (poly)alkoxy structure, and polymerizable ether sulfate-type ammonium salts; nonionic surfactants such as alkyl esters of polyethylene glycol, alkyl phenyl ethers of polyethylene glycol, and alkyl ethers of polyethylene glycol; and fluorine-based surfactants such as perfluorobutyl sulfonates, perfluoroalkyl group-containing phosphate esters, perfluoroalkyl group-containing carboxylates, and perfluoroalkylethylene oxide adducts. At least one selected from these can be used.
[0047] Specific examples of the polymerization initiator include water-soluble polymerization initiators such as lithium persulfate, potassium persulfate, sodium persulfate, ammonium persulfate, and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] tetrahydrate; and oil-soluble polymerization initiators such as cumene hydroperoxide, benzoyl peroxide, tert-butyl hydroperoxide, acetyl peroxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, azobisisobutyronitrile, and 1,1'-azobis(cyclohexanecarbonitrile). Of these, potassium persulfate, sodium persulfate, ammonium persulfate, cumene hydroperoxide, or tert-butyl hydroperoxide may be used. The proportion of the polymerization initiator used is not particularly limited, but is appropriately set in consideration of the monomer composition, the pH of the polymerization reaction system, the combination of other additives, etc.
[0048] Specific examples of chain transfer agents include alkyl mercaptans such as n-hexyl mercaptan, n-octyl mercaptan, tert-octyl mercaptan, n-dodecyl mercaptan, tert-dodecyl mercaptan, and n-stearyl mercaptan; xanthogen compounds such as dimethyl xanthogen disulfide and diisopropyl xanthogen disulfide; thiuram compounds such as terpinolene, tetramethylthiuram disulfide, tetraethylthiuram disulfide, and tetramethylthiuram monosulfide; 2,6-di-tert-butyl-4-methylphenol, styrenated phenol, and the like. Examples of the monomer include phenol compounds; allyl compounds such as allyl alcohol; halogenated hydrocarbon compounds such as dichloromethane, dibromomethane, and carbon tetrabromide; vinyl ether compounds such as α-benzyloxystyrene, α-benzyloxyacrylonitrile, and α-benzyloxyacrylamide; as well as triphenylethane, pentaphenylethane, acrolein, methacrolein, thioglycolic acid, 2-ethylhexyl thioglycolate, thiomalic acid, 2-ethylhexyl thioglycolate, and α-methylstyrene dimer, and one or more selected from these can be used.
[0049] The emulsion polymerization step is preferably carried out under conditions of a polymerization temperature of 40 to 80° C. and a polymerization time of 2 to 4 hours.
[0050] After the emulsion polymerization is completed, it is preferable to neutralize the dispersion to a pH of about 5 to 10 by adding a neutralizing agent. The neutralizing agent to be used is not particularly limited, but examples thereof include metal hydroxides such as sodium hydroxide and potassium hydroxide, ammonia, and amine compounds. The pH of the dispersion is set in the range of 5 to 10 to improve the blending stability of the dispersion, preferably 6 to 9, and more preferably 7 to 8.5. If the total solid content concentration in the emulsion polymerization step is 50% by mass or less, the reaction can proceed with good dispersion stability, but is preferably 45% by mass or less, and more preferably 40% by mass or less. In addition, by concentrating after the neutralization treatment, the particle stability can be further improved while achieving high solid fractionation.
[0051] 1.2. Multivalent anions (B) The composition according to the present embodiment may contain a polyvalent anion (B). The concentration of the polyvalent anion (B) in the composition according to the present embodiment is preferably 300 ppm to 2,000 ppm, more preferably 400 ppm to 1,000 ppm, and particularly preferably 500 ppm to 800 ppm. When the concentration of the polyvalent anion (B) in the composition is within the above range, the dispersion stability of the polymer particles (A) is improved, so that the storage stability of the composition is improved and aggregation of the polymer particles (A) due to shock when mixed with other components such as an organic solvent can be suppressed.
[0052] The polyvalent anion (B) is not particularly limited as long as it is a polyvalent anion, and may be a carbonate ion (CO 2- ), sulfate ion (SO4 2- ), phosphate ion (PO4 3- ), citrate ion, ascorbate ion, isoascorbate ion, oxalate ion, etc. Among these, sulfate ion (SO4 2- ) is preferable. Sulfate ion (SO4 2- By containing a predetermined amount of (A), the dispersion stability of the polymer particles (A) can be effectively improved, and therefore the storage stability of the composition is dramatically improved.
[0053] In order to generate the polyvalent anion (B) in the composition according to the present embodiment, a means for dissolving a compound containing the polyvalent anion (B) in the composition can be used. Examples of such compounds containing the polyvalent anion (B) include sulfuric acid, phosphoric acid, iron sulfate (ferrous sulfate, sulfuric acid, etc.). Examples of suitable ferric sulfate include aluminum sulfate, aluminum potassium sulfate, magnesium sulfate, magnesium nitrate, magnesium potassium sulfate, and zinc sulfate. Among these, sulfuric acid is preferred.
[0054] 1.3. Liquid medium (C) The composition according to the present embodiment contains a liquid medium (C). The liquid medium (C) is preferably an aqueous medium containing water. The aqueous medium can contain a non-aqueous medium other than water. Examples of the non-aqueous medium include amide compounds, hydrocarbons, alcohols, ketones, esters, amine compounds, lactones, sulfoxides, and sulfone compounds, and one or more selected from these can be used. When the liquid medium (C) contains water and a non-aqueous medium, it is preferable that 90% by mass or more of the total amount of the liquid medium (C) is water, and more preferably 98% by mass or more of water. By using an aqueous medium as the liquid medium (C), the composition according to the present embodiment has a low degree of adverse effect on the environment and is safer for the handling workers.
[0055] The content of the non-aqueous medium in the aqueous medium is preferably 10% by mass or less, more preferably 5% by mass or less, and particularly preferably substantially free of the aqueous medium, based on 100% by mass of the aqueous medium. Here, "substantially free of the non-aqueous medium" means that the non-aqueous medium is not intentionally added as a liquid medium, and may include a non-aqueous medium that is inevitably mixed in when the composition is prepared.
[0056] 1.4. Other Additives The composition according to the present embodiment may contain additives other than the above-mentioned components as necessary. Examples of such additives include a thickener, a filler, a preservative, and a pH adjuster.
[0057] <Thickener> Examples of thickeners include cellulose compounds such as carboxymethylcellulose, methylcellulose, and hydroxypropylcellulose; ammonium salts or alkali metal salts of the above cellulose compounds; polycarboxylic acids such as poly(meth)acrylic acid and modified poly(meth)acrylic acid; alkali metal salts of the above polycarboxylic acids; polyvinyl alcohol (co)polymers such as polyvinyl alcohol, modified polyvinyl alcohol, and ethylene-vinyl alcohol copolymers; water-soluble polymers such as saponified copolymers of unsaturated carboxylic acids such as (meth)acrylic acid, maleic acid, and fumaric acid with vinyl esters. Particularly preferred thickeners among these include alkali metal salts of carboxymethylcellulose and alkali metal salts of poly(meth)acrylic acid.
[0058] Commercially available products of these thickeners include, for example, alkali metal salts of carboxymethylcellulose such as CMC1120, CMC1150, CMC2200, CMC2280, and CMC2450 (all manufactured by Daicel Corporation).
[0059] When the composition according to the present embodiment contains a thickener, the amount of the thickener used is preferably 5% by mass or less, and more preferably 0.1 to 3% by mass, based on the total solid content of the composition.
[0060] <Filler> The composition according to the present embodiment may contain a filler, which may improve the hardness of the coating film when it is formed into a coating film. Examples of the filler include organic fillers and inorganic fillers. Specific examples of the organic filler include polyamide fine particles such as nylon 6, nylon 12, and nylon 66; fluorine-based fine particles such as tetrafluoroethylene and vinylidene fluoride; polyethylene fine particles such as tetrafluoroethylene and vinylidene fluoride; Olefin-based fine particles such as lens and polypropylene; polyester-based fine particles such as polyethylene terephthalate and polyethylene naphthalate; cross-linked particles such as divinylbenzene and polyfunctional acrylate; and rubber fine particles such as natural rubber, isoprene rubber, and acrylic rubber. Specific examples of the inorganic filler include fused spherical silica, fumed silica, sol-gel silica, etc., aluminum oxide, aluminum hydroxide, calcium carbonate, calcium hydroxide, barium sulfate, barium carbonate, magnesium oxide, magnesium hydroxide, and other inorganic fillers derived from minerals such as talc and mica. One or more of these can be used.
[0061] <Preservative> The composition according to this embodiment contains a preservative, which can suppress the growth of bacteria, molds, etc. and the generation of foreign substances when the composition is stored. Specific examples of the preservative include 1,2-benzisothiazolin-3-one, 2-methyl-4,5-trimethylene-4-isothiazolin-3-one, 2-methyl-4-isothiazolin-3-one, 5-chloro-2-methyl-4-isothiazolin-3-one, N-n-butyl-1,2-benzisothiazolin-3-one, 2-n-octyl-4-isothiazolin-3-one, 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one, etc. One or more of these can be used.
[0062] <pH adjuster> The composition according to this embodiment may adjust the pH to 5-9 by adding a pH adjuster. By adjusting the pH to 5-9, the dispersion stability of the polymer particles (A) may be improved, and the storage stability may be excellent. Examples of the pH adjuster include acidic compounds such as hydrochloric acid, phosphoric acid, sulfuric acid, acetic acid, and formic acid; and basic compounds such as potassium hydroxide, ethylenediamine, monoethanolamine, TMAH (tetramethylammonium hydroxide), TEAH (tetraethylammonium hydroxide), and ammonia.
[0063] In the present invention, pH refers to hydrogen ion exponent, and its value can be measured using a commercially available pH meter (for example, a tabletop pH meter manufactured by Horiba, Ltd.) under conditions of 25° C. and 1 atmospheric pressure.
[0064] 2. Example The present invention will be described below with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" and "%" are by weight unless otherwise specified.
[0065] 2.1 Example 1 2.1.1. Synthesis of polymer particles (A) After thoroughly replacing the inside of a 3L separable flask with nitrogen, 50.0 parts by mass of ion-exchanged water and 0.1 parts by mass of ammonium persulfate were charged. The inside temperature was adjusted to 80°C while stirring, and 60.0 parts by mass of ion-exchanged water, 50.0 parts by mass of methyl methacrylate (MMA), 46.0 parts by mass of 2-ethylhexyl acrylate (EHA), 3.0 parts by mass of methacrylic acid (MAA), 1.0 parts by mass of allyl methacrylate (AMA), and 2.0 parts by mass of emulsifier "Neopelex G-25" (trade name, manufactured by Kao Corporation) were mixed and stirred in a separate container to prepare an emulsion, and the obtained emulsion was continuously dropped into the above reaction container over 3 hours. After the dropwise addition, the mixture was stirred for another 3 hours at 80°C, cooled to 40°C, and 0.1 parts by mass of ammonia water was added to obtain an aqueous dispersion of polymer particles (A).
[0066] 2.1.2. Measurement of THF insolubles Approximately 10 g of the obtained aqueous dispersion was weighed into a Teflon petri dish with a diameter of 8 cm and dried at 120°C for 1 hour to form a membrane. The polymer particles were immersed in 50 mL of THF and shaken for 24 hours at 25° C. The THF phase was then filtered through a 300-mesh wire screen to separate the insoluble matter, and the soluble THF was evaporated and removed to obtain a residue weight (Y(g)). The THF insoluble matter was calculated from the weight by the following formula (2), and the THF insoluble matter of the polymer particles was found to be 95%. THF insolubles (%) = ((1-Y) / 1) × 100 (2)
[0067] 2.1.3. Preparation of the Composition The aqueous dispersion containing the polymer particles (A) obtained above was repeatedly filtered through a filter until the amount of particles having a particle diameter of 0.5 μm or more reached the value shown in Table 1 below, thereby preparing a composition of Example 1.
[0068] The content of polymer particles (coarse particles) having a particle size of 0.5 μm or more in the obtained composition was measured using a particle size distribution measuring device (Accusizer 780A, manufactured by Entegris, Inc.). 5 The number of cells was 1 / mL.
[0069] In addition, the particle size distribution of the obtained composition was measured using a particle size distribution measuring device (manufactured by Otsuka Electronics Co., Ltd., model "FPAR-1000") using the dynamic light scattering method as the measurement principle, and the number average particle diameter (D50) was calculated from the particle size distribution, and the number average particle diameter (D50) was 60 nm.
[0070] Evaluation method <Evaluation of Settling Property> Generally, such compositions are stored in large quantities in a factory for use, and the stored compositions are consumed in succession as needed, without allowing the properties of the composition when first consumed to change after long-term storage due to settling of polymer particles, etc.
[0071] (Evaluation method) 100 g of the composition prepared above was filled into a plastic bottle and stored in a refrigerator set at 5°C for one month. After storage, the composition was visually observed and evaluated. The evaluation criteria are as follows. The results are shown in Table 1. (Evaluation Criteria) If no sedimentation of polymer particles is observed, it is considered to be good and rated as "A". If any sedimentation of polymer particles is observed, the product is deemed defective and given a grade of "B". It was written as follows.
[0072] <Evaluation of coating drying properties> In various applications, the composition is often dried to form a coating at a temperature below the boiling point of the liquid medium (C). For example, when the composition is mixed with a plasticizer such as Texanol and the resulting mixture is dried at 80°C, whitening of the coating is not acceptable and the resulting coating is required to be transparent.
[0073] (Evaluation method) 0.1 g of Texanol was added as a plasticizer to 10 g of the composition prepared above, and 10.1 g of the resulting mixture was weighed into a Teflon petri dish with a diameter of 8 cm and dried at 80°C for 2 hours to form a film. The resulting coating film was visually observed and evaluated. The evaluation criteria are as follows. The results are also shown in Table 1. (Evaluation Criteria) If the resulting coating is transparent, it is considered good and given an "A" rating. If the resulting coating is cloudy and opaque, it is deemed defective and rated "B". It was written as follows.
[0074] 2.2. Examples 2 to 12 and Comparative Examples 1 to 2 In "2.1.1. Synthesis of polymer particles (A)" of Example 1, the monomer composition and the types and amounts of the chain transfer agent, emulsifier, polymerization initiator, and additives were changed as shown in Tables 1 and 2 below, and the number of times of filter filtration was appropriately changed, but otherwise, an aqueous dispersion containing polymer particles having the composition shown in Tables 1 and 2 below was prepared in the same manner as in Example 1. Otherwise, a composition was prepared and evaluated in the same manner as in Example 1 above.
[0075] 2.3.Evaluation Results Tables 1 and 2 below show the monomer composition, types and amounts of chain transfer agents, emulsifiers, polymerization initiators, and additives used in the synthesis of polymer particles in each Example and Comparative Example, the properties of the polymer particles, and the evaluation results.
[0076] [Table 1]
[0077] [Table 2]
[0078] The following products or reagents were used for each component in Tables 1 and 2 above. <Methyl (meth)acrylate> MMA: Methyl methacrylate (manufactured by Mitsubishi Chemical Corporation, product name "Acryester M") <(Meth)acrylic acid alkyl (C4-C10) ester> BA: Butyl acrylate (manufactured by Mitsubishi Chemical Corporation, product name "Butyl acrylate") EHA: 2-Ethylhexyl acrylate (manufactured by Nippon Shokubai Co., Ltd., product name "2-Ethylhexyl acrylate") <Other monomers> ST: Styrene (NS Styrene Monomer Co., Ltd., product name "Styrene Monomer") EMA: Ethyl methacrylate (manufactured by Mitsubishi Chemical Corporation, product name "Acryester E") EDMA: Ethylene glycol dimethacrylate (manufactured by Mitsubishi Chemical Corporation, product name "Acryester ED") AMA: Allyl methacrylate (manufactured by Mitsubishi Chemical Corporation, product name "Acryester A") AA: Acrylic acid (manufactured by Toagosei Co., Ltd., product name "acrylic acid") · MAA: Methacrylic acid (manufactured by Mitsubishi Chemical Corporation, product name "MAA") NaSS: Sodium p-styrenesulfonate (manufactured by Tosoh Finechem Corporation, product name "Spinomer Nass") HEMA: 2-hydroxyethyl methacrylate (manufactured by Mitsubishi Chemical Corporation, product name "Acryester HO") <Chain transfer agent> NDM: n-dodecyl mercaptan (manufactured by Kaneda Co., Ltd., product name "N-dodecyl mercaptan") <Emulsifier> SDS: Sodium dodecyl sulfate (Kao Corporation, product name "EMAL 2FG") E-118B: Sodium polyoxyethylene alkyl ether sulfate (manufactured by Kao Corporation, product name "Latemul E-118B") SDBS: Sodium dodecylbenzenesulfonate (manufactured by Kao Corporation, product name "Neopelex G-25") JONCRYL 60J: Ammonium salt of modified styrene-acrylic resin (manufactured by BASF Japan Ltd., product name "JONCRYL 60J") SR-1025: (Manufactured by ADEKA Corporation, product name "ADEKA REASOAP SR-1025", ammonium salt of α-sulfo-ω-(1-alkoxy)methyl-2-(2-propenyloxy)ethoxy-poly(oxy-1,2-ethanediyl)) E147: Poly(oxyethylene) dodecyl ether (Kao Corporation, product name "Emulgen 147") <Polymerization initiator> APS: Ammonium persulfate (manufactured by Mitsubishi Gas Chemical Company, Inc., product name "Ammonium persulfate") <Additives> IPA: Isopropanol (Tokuyama Corporation, product name "Tokuso IPA") Ammonia water: (manufactured by Taisei Kako Co., Ltd., product name "Triethanolamine", pH adjuster)
[0079] According to the evaluation results in Tables 1 and 2, the compositions according to the present invention shown in Examples 1 to 12 had excellent storage stability, with no sedimentation of polymer particles even after storage for one month. In addition, the compositions according to the present invention shown in Examples 1 to 12 had transparent coatings that were dried at 80°C for two hours without whitening.
[0080] In contrast, the content of polymer particles (A) having a particle size of 0.5 μm or more is 0.2 × 10 5 It was found that the composition shown in Comparative Example 1, in which the content was 1 / mL, caused the coating film to whiten when dried at 80° C. for 2 hours. 7000 pieces x 105 In the composition shown in Comparative Example 2, in which the concentration was 1 / mL, sedimentation of the polymer particles (A) was observed after storage for one month.
[0081] The present invention is not limited to the above-described embodiments, and various modifications are possible. For example, the present invention includes configurations that are substantially the same as those described in the embodiments (for example, configurations with the same functions, methods, and results, or configurations with the same purpose and effect). The present invention also includes configurations in which non-essential parts of the configurations described in the embodiments are replaced. The present invention also includes configurations that achieve the same effects as the configurations described in the embodiments, or configurations that can achieve the same purpose. The present invention also includes configurations in which publicly known technology is added to the configurations described in the embodiments.
Claims
1. A composition comprising polymer particles (A) and a liquid medium (C), The polymer particles (A) have a repeating unit (Ma) derived from methyl (meth)acrylate and a repeating unit (Mb) represented by the following general formula (1), The content of polymer particles (A) having a particle size of 0.5 μm or more in the composition is 1×10 5 pieces / mL ~ 5000×10 5 The composition, 【Chemistry 1】 (In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents an alkyl group having 4 to 10 carbon atoms.
2. The composition according to claim 1, wherein the number average particle size of the polymer particles (A) is 30 nm to 600 nm.
3. The composition according to claim 1 or 2, wherein the THF-insoluble content of the polymer particles (A) is 60 mass% or more based on 100 mass% of the polymer particles (A).
4. The composition according to claim 1 or claim 2, further comprising 300 ppm to 2,000 ppm of a polyvalent anion (B).
5. The polyvalent anion (B) is SO 4 2- The composition of claim 4 ,
Citation Information
Patent Citations
White ink and inkjet recording method
JP2022124473A
Ink and ink-jet recording method
WO2021006211A1